2018
DOI: 10.3233/jhd-170280
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal Dysfunction in Presymptomatic Mutation Carriers and Patients with Huntington’s Disease

Abstract: Our study demonstrated significant bowel dysfunction in HD patients. We propose these symptoms to be of central autonomic origin, although we cannot exclude effects of medication. These often neglected symptoms in HD subjects require greater attention from physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Alongside progressive central pathology resulting in neurodegeneration and cognitive decline 3 , 4 , HD pathology is defined by weight loss 27 29 . It has been pointed out that presymptomatic mutation carriers and patients with Huntington's disease show upper GI tract problems 30 , bladder 31 and bowel dysfunction 32 and that the severity of dysfunction correlates with poor quality of life and depression. Similarly, van der Burg and colleagues found impaired gut motility, diarrhea, and malabsorption of food in R6/2 mice 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Alongside progressive central pathology resulting in neurodegeneration and cognitive decline 3 , 4 , HD pathology is defined by weight loss 27 29 . It has been pointed out that presymptomatic mutation carriers and patients with Huntington's disease show upper GI tract problems 30 , bladder 31 and bowel dysfunction 32 and that the severity of dysfunction correlates with poor quality of life and depression. Similarly, van der Burg and colleagues found impaired gut motility, diarrhea, and malabsorption of food in R6/2 mice 9 .…”
Section: Discussionmentioning
confidence: 99%
“…HD is the only disease in the group in which gastrointestinal (GI) dysfunction is a major symptom. Signs of this dysfunction can appear early, before evidence of CNS neurodegeneration is apparent ( Kobal et al, 2018 ; Wood et al, 2008 ; Andrich et al, 2009 ). Similar symptoms are seen in mouse models of HD where they are associated with a decrease in the length of the colon ( Stan et al, 2020 ), the mucosal thickness and villus length ( van der Burg et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anorectal dysfunction, manifesting as incontinence or constipation, is significantly more prevalent in individuals with HD compared with healthy controls and may even arise in the premanifest stage 66 . Several studies have shown no evidence of degeneration in Onuf's nucleus, although anal sphincter EMG studies do demonstrate decreased tonic sphincter activity and impaired voluntary activation 67 …”
Section: Primary Movement Disorders With Associated Gi Symptomsmentioning
confidence: 99%